Interfacial nanoarchitectonics for ZIF-8 membranes with enhanced gas separation - Chen, Season S.; Yang, Zhen-Jie; Chang, Chia-Hao; Koh, Hoong-Uei; Al-Saeedi, Sameerah I.; Tung, Kuo-Lun; Wu, Kevin C.-W. (Beilstein Journal of Nanotechnology, 2022)
Metal-organic framework (MOF) membranes are potentially useful in gas separation applications. Conventional methods of MOF membrane preparation require multiple steps and high-pressure conditions. In this study, a reliable one-step interfacial synthesis method under atmospheric pressure has been developed to prepare zeolitic imidazolate framework-8 (ZIF-8) membranes supported on porous α-Al2O3 disks. To obtain optimal ZIF-8 membranes, three reaction parameters were investigated, namely, reaction temperature, reaction time, and concentration of the organic linker (i.e., 2-methylimidazole). The growth of ZIF-8 membranes under various parameters was evaluated by field-emission scanning electron microscopy, and the optimal synthesis conditions were determined (i.e., 80 °C for 12 h in 50 mM of 2-methylimidazole). The as-synthesized ZIF-8 membranes were then applied to CO2/N2 gas separation, which exhibited a maximum separation factor of 5.49 and CO2 gas permeance of 0.47 × 10−7 mol·m−2·s−1·Pa−1.
Keywords: defect-free; gas separation; interfacial synthesis; metal-organic frameworks; ZIF membranes